2014
DOI: 10.1016/j.ijid.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enteric viral and bacterial pathogens associated with paediatric diarrhoea in Goroka, Papua New Guinea

Abstract: This study demonstrates that Shigella and rotavirus are the major pathogens associated with acute paediatric gastroenteritis in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Several authors suggest that rotavirus could be the main cause of enteric disease in rabbits and also be implicated as the etiological agent of severe enteric outbreaks 16,35 . Lavazza et al 14 identified rotavirus in rabbits by electron microscopy (16.0%), detecting 3.3% to 36.6% in humans 8,27,37 , our findings show the presence of rotavirus in fewer cases (10.3%). The concomitant identification of rotavirus and other pathogens was detected in 5/6 (83.3%) samples.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Several authors suggest that rotavirus could be the main cause of enteric disease in rabbits and also be implicated as the etiological agent of severe enteric outbreaks 16,35 . Lavazza et al 14 identified rotavirus in rabbits by electron microscopy (16.0%), detecting 3.3% to 36.6% in humans 8,27,37 , our findings show the presence of rotavirus in fewer cases (10.3%). The concomitant identification of rotavirus and other pathogens was detected in 5/6 (83.3%) samples.…”
Section: Discussionsupporting
confidence: 55%
“…(26.6%), enteropathogenic E. coli (8.5%), Salmonella spp. were found below the limit of detection 27 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, RoV coinfection was infrequent in younger children and peaked in infants between 7 and 12 months old. These results are comparable with the percentages of mixed infections detected in earlier reports, which found a prevalence of 2 % to 19 % [32][33][34]. The reason to this prevalence is the role of maternal antibodies in the protection of infants and the immunity acquired through previous exposure [23,29,35].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, clinical presentation of patient with AGE is not generally indicative of a pathogen. It has been reported that symptoms, the length of hospitalization, and the number of diarrhea episodes are not significantly different for the different infectious agents [27,33,36].…”
Section: Discussionmentioning
confidence: 97%